Uang dan Kebijakan Moneter Islam dalam Mewujudkan Stabilitas Moneter yang Berkelanjutan - Muhammad Khaeru Fathurrohman; Mahda Rihhadatul Aisy; Najmudin Najmudin (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2026)
Introduction: Currently, the global economy is in a state of crisis, characterized by widespread poverty, exploitation, regional and international economic inequality, unbalanced production patterns, and the unsustainable use of natural resources. In contrast, during the era of Islamic governance, the dinar and dirham were established as legitimate means of exchange to achieve sustainable monetary stability. Research Methods: This study employs a qualitative research method in the form of a literature review. Books, scientific journals, and websites serve as secondary data sources for this study. Result: The dinar and dirham have been in use since the time of the Prophet Muhammad (peace be upon him), through the era of the Caliphate, and into the Umayyad and Abbasid dynasties. From the very beginning, Islamic governments implemented monetary policies that established the dinar and dirham as the official monetary standard. This policy had a positive impact on the growth of goods and services within a country, thereby creating a balance in aggregate supply and demand. In addition, the welfare and employment opportunities of the people continued to improve. In this regard, the dinar and dirham are considered stable currencies in preventing economic downturns, inflation, and recessions; unlike the paper money used today.